Rape Co-occurrence: Do Additional Crimes Affect Victim Reporting and Police Clearance of Rape? - Addington, Lynn A. (Journal of quantitative criminology, 2008)
Despite the increased research attention given to rape and violence against women, little is known about rape co-occurrence, or rape incidents that involve another crime. Although previous research has found certain incident characteristics increase the likelihood that a victim reports her rape to police and that the offender is arrested and prosecuted, the relationship between co-occurrence and these responses is unknown. Given this gap in the literature, the main goal of the present research is to provide an initial understanding of rape co-occurrence and its effect on victim reporting and police clearance. To explore these issues, this study uses two national data sources that collect the requisite incident-level information: the National Crime Victimization Survey and the Uniform Crime Reporting Program’s National Incident-Based Reporting System. Few rapes are found to co-occur with other crimes. When rapes do occur with other crimes, though, they are more likely than solo-occurring rapes to involve weapons, strangers, additional injury to the victim, and multiple offenders. Rapes that co-occur also are more likely to be reported to police and cleared by police than rapes that occur with no other crimes.